Preparation and application of biomass-based supramolecular deep eutectic gel electrolyte

CN122931022APending Publication Date: 2026-10-16SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611232273.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的目的就是为了弥补现有技术的不足,提供了生物质基超分子低共熔凝胶电解质的制备与应用,它能够解决现有生物质基凝胶电解质离子传输效率不足、高压稳定性有限以及锂金属界面副反应严重的问题

Benefits of technology

本发明通过双锂盐构建双阴离子低共熔溶剂并重构Li+第一溶剂化层,实现提升Li+迁移数至0.75、减轻浓差极化并为电极界面提供F、N、B成膜元素的效果,通过低共熔溶剂破坏生物质材料原有链间氢键与有序结构,经冷却自组装形成可逆氢键与离子偶极动态超分子网络,实现构建连续Li+传输通道并自适应电极充放电体积变化的效果,通过双阴离子溶剂化结构诱导电极表面形成富含LiF、Li3N及LixBᵧOFz的致密界面层,实现抑制界面副反应、拓宽电化学窗口至5.2V并诱导均匀锂沉积的效果,通过无共价交联的冷却自组装工艺,实现简化制备流程并兼容现有锂电池制造制程的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931022A_ABST
    Figure CN122931022A_ABST
Patent Text Reader

Abstract

The application discloses preparation and application of a biomass-based supermolecular eutectic gel electrolyte, and relates to the technical field of electrochemical energy storage and gel polymer electrolyte; lithium salt 1, lithium salt 2 and a hydrogen bond donor are mixed and heated to form a homogeneous and transparent double-anion eutectic solvent; a biomass material is added as a skeleton to form a precursor solution, and the precursor solution is cooled and self-assembled on a porous fiber carrier to obtain the biomass-based supermolecular eutectic gel electrolyte; the double-anion eutectic solvent is constructed by using double lithium salts, and Li + The first solvation layer realizes the effects of improving Li + The migration number to 0.75, reducing concentration polarization and providing F, N and B film-forming elements for the electrode interface, the original interchain hydrogen bond and ordered structure of the biomass material are destroyed by the eutectic solvent, a reversible hydrogen bond and ionic dipole dynamic supramolecular network is formed through cooling and self-assembly, and the effects of constructing a continuous Li + transport channel and self-adapting to the volume change of electrode charging and discharging are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of electrochemical energy storage and gel polymer electrolyte technology, specifically the preparation and application of biomass-based supramolecular eutectic gel electrolytes. Background Technology

[0002] Lithium metal has a capacity of 3860 mAh·g -1 Lithium's high theoretical specific capacity and low reduction potential of approximately -3.04V relative to the standard hydrogen electrode make it an ideal anode material for constructing high-energy-density secondary batteries. However, lithium metal is prone to dendrite formation and dead lithium formation during repeated deposition and stripping. Meanwhile, traditional ether- or carbonate-based liquid electrolytes are flammable and volatile, and continuously react with lithium metal, leading to increased interfacial impedance, shortened cycle life, and even internal short circuits and thermal runaway. Gel polymer electrolytes combine the interfacial wettability of liquid electrolytes with the structural stability of solid electrolytes. Gel electrolytes composed of eutectic solvents and polymer backbones also offer advantages such as low volatility, non-flammability, and ease of component design and processing. However, existing eutectic gel electrolytes often struggle to balance room-temperature ionic conductivity, lithium-ion transference number, high voltage stability, and lithium metal interfacial compatibility. The protective layer formed at the positive and negative electrode interfaces by a solvation structure dominated by a single lithium salt anion often lacks sufficient inorganic phase content, failing to suppress interfacial side reactions and dendrite growth in the long term.

[0003] Biomass materials are widely available, renewable, and contain abundant polar groups, making them suitable as electrolyte frameworks. Hydroxyethyl cellulose (HEC) exhibits good solubility and chain flexibility, and its hydroxyl and hydroxyethyl groups can form hydrogen bonds and ion dipole interactions with lithium ions and eutectic components. However, the existing hydrogen bonds and locally ordered structure between cellulose chains can restrict ion entry and migration; simultaneously, hydroxyl groups may initiate side reactions at the lithium metal interface. Therefore, relying solely on the cellulose framework is insufficient to obtain an electrolyte that simultaneously possesses high conductivity, a wide electrochemical window, and long cycling performance.

[0004] However, existing eutectic gel electrolytes cannot simultaneously achieve room temperature ionic conductivity, lithium-ion transference number, high voltage stability, and lithium metal interface compatibility. The inorganic phase content of the protective layer formed at the positive and negative electrode interfaces by the solvation structure dominated by a single lithium salt anion is insufficient, which cannot suppress interfacial side reactions and dendrite growth in the long term. The interchain hydrogen bonds and local ordered structure of the biomass framework material itself restrict the entry and migration of ions, and the polar hydroxyl groups on the material surface are also prone to initiating side reactions at the lithium metal interface. It is impossible to obtain a gel electrolyte with high conductivity, wide electrochemical window, and long cycling performance by relying solely on a single biomass framework. Therefore, the development and application of biomass-based supramolecular eutectic gel electrolytes are of great significance. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and to provide the preparation and application of biomass-based supramolecular eutectic gel electrolytes. It can solve the problems of insufficient ion transport efficiency, limited high-pressure stability and serious side reactions at the lithium metal interface of existing biomass-based gel electrolytes.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: preparation of biomass-based supramolecular eutectic gel electrolyte, the preparation comprising the following method steps: S1. Lithium salt 1 and lithium salt 2, which act as hydrogen bond acceptors, are mixed with hydrogen bond donors and heated and stirred until a homogeneous and transparent dianionic eutectic solvent is formed. S2. Add biomass material as a framework network to a dianionic eutectic solvent, and heat and stir until a homogeneous and viscous electrolyte precursor is formed. S3. The electrolyte precursor is applied to a porous fiber carrier and cooled to allow the biomass material and the dianionic eutectic solvent to self-assemble in situ through hydrogen bonding and ionic dipole interaction, thus obtaining a biomass-based supramolecular eutectic gel electrolyte.

[0007] Further, in step S1, lithium salt 1 is selected from lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, and lithium difluorooxalate borate; lithium salt 2 is selected from lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, and lithium difluorooxalate borate; the hydrogen bond donor is selected from one or more of succinic anionyl, dimethylmalonium, N-methylacetamide, and N-methyl-2,2,2-trifluoroacetamide; and the biomass material in step S2 is selected from one or more of hydroxyethyl cellulose, lignin, cyclodextrin, chitosan, and alginate.

[0008] Furthermore, in step S1, the molar ratio of lithium salt 1 to lithium salt 2 is 1:0.1-0.5, the molar ratio of lithium salt 1 to hydrogen bond donor is 1:1-5, and the heating and stirring temperature is 50-70℃; the optimal molar ratio is 1:0.4:4, under which the two anions can fully participate in the coordination of the first solvation layer of lithium ions, while maintaining the homogeneity of the system and the degree of lithium salt dissociation, avoiding the decrease in ionic conductivity caused by the excess of the second lithium salt; the optimal heating and stirring temperature is 60℃, which can ensure the complete dissolution of the components while maintaining the structural stability of the eutectic system.

[0009] Furthermore, in step S2, the amount of biomass material added is 3-10 wt% of the total mass of the dianionic eutectic solvent, and the biomass material is a low-crystallinity or low-polymerization biomass material; the optimal addition amount is 7 wt%, and the optimal balance between ion transport performance and gel mechanical properties can be obtained when low-polymerization hydroxyethyl cellulose is selected; low-crystallinity and low-polymerization biomass materials can weaken the original hydrogen bonding between their own molecular chains, promote the entry of solvated lithium ions into the chain and build continuous migration channels.

[0010] Furthermore, before or after adding biomass materials, fluoroethylene carbonate is added to the diaionic eutectic solvent as a film-forming additive. Fluoroethylene carbonate does not participate in the construction of the supramolecular gel network, but can work synergistically with the diaionic solvation structure to regulate the composition and compactness of the electrode interface film, further improving the proportion of inorganic phase and long-term stability of the interface layer without changing the original gelation mechanism.

[0011] Furthermore, the porous fiber carrier in step S3 is a glass fiber membrane, and the electrolyte precursor is applied to the porous fiber carrier by one of the following methods: dripping, impregnation, scraping, or in-situ infusion.

[0012] Furthermore, no covalent crosslinking agent, monomer, or polymerization initiator is added during the preparation process of step S3. After cooling, the electrolyte precursor forms a dynamic supramolecular network through reversible non-covalent interactions, which include hydrogen bonding and ion dipole interactions. The entire gelation process is completed solely through cooling-triggered non-covalent self-assembly, eliminating the need for additional processes such as UV curing and thermally initiated polymerization. This allows for direct adaptation to existing in-situ liquid injection encapsulation processes for lithium batteries.

[0013] The present invention also provides a biomass-based supramolecular eutectic gel electrolyte prepared by the above-described method for preparing a biomass-based supramolecular eutectic gel electrolyte, wherein the gel electrolyte comprises lithium salt 1, lithium salt 2 and a hydrogen bond donor, the first solvation layer of lithium ions is a coordination structure of lithium ion-anion 1-anion 2-hydrogen bond donor, and the biomass material constitutes a supramolecular network with reversible hydrogen bonding and ionic dipole interaction.

[0014] Furthermore, the gel electrolyte has an ionic conductivity of 1.0-2.5 mS·cm at 30°C. -1 The lithium-ion transference number is 0.50-0.80, and the electrochemical stability window is not lower than 5.0V. After the gel electrolyte is in contact with the lithium metal electrode and undergoes charge-discharge cycles, a layer containing LiF, Li3N, and Li is formed on the surface of the lithium metal anode. x The BᵧOFz inorganic phase solid electrolyte interface layer forms a positive electrode surface containing LiF, Li3N and Li. xBᵧOFz inorganic phase positive electrolyte interface layer; under optimal system conditions, ionic conductivity can reach 1.66 mS·cm at 30℃. -1 The lithium-ion transference number can reach 0.75, and the electrochemical stability window can reach 5.2V, which can meet the application requirements of high-voltage lithium cobalt oxide cathodes. The formed interface layer consists of an inorganic inner layer with high mechanical strength and an organic outer layer with elastic buffering capacity. The inner layer provides a fast lithium-ion conduction path, and the outer layer buffers the volume deformation of lithium deposition and stripping, which can maintain the integrity of the interface for a long time.

[0015] This invention also provides the application of a biomass-based supramolecular eutectic gel electrolyte in lithium metal batteries. The lithium metal battery includes a positive electrode, a lithium metal negative electrode, and the gel electrolyte disposed between the positive electrode and the lithium metal negative electrode. The active material of the positive electrode is lithium iron phosphate or lithium cobalt oxide. The lithium iron phosphate lithium metal battery assembled using this gel electrolyte can achieve a capacity retention of 75.9% after 3000 cycles at 1C rate, and the lithium cobalt oxide lithium metal battery can achieve a capacity retention of 88.7% after 1000 cycles at a cutoff voltage of 4.4V. The electrolyte itself has self-extinguishing and non-flammable properties, and the small molecule components can be effectively suppressed by encapsulating them through the gel network, significantly improving the thermal safety performance of the battery.

[0016] Compared with existing technologies, the preparation and application of this biomass-based supramolecular eutectic gel electrolyte have the following advantages: This invention constructs a dual-anionic eutectic solvent using a dual lithium salt and reconstructs Li + The first solvation layer enhances Li + The migration number is reduced to 0.75, concentration polarization is alleviated, and F, N, and B film-forming elements are provided to the electrode interface. The original interchain hydrogen bonds and ordered structure of the biomass material are disrupted by a eutectic solvent, and reversible hydrogen bonds and ionic dipole dynamic supramolecular networks are formed through cooling self-assembly, thus achieving the construction of continuous Li. + The transmission channel adapts to the volume changes during electrode charging and discharging, and induces the formation of LiF, Li3N, and Li-rich compounds on the electrode surface through a dual anion solvation structure. x The dense interface layer of BᵧOFz achieves the effects of suppressing interfacial side reactions, widening the electrochemical window to 5.2V, and inducing uniform lithium deposition. Through a non-covalent crosslinking cooling self-assembly process, it simplifies the preparation process and is compatible with existing lithium battery manufacturing processes.

[0017] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0019] Figure 1 This is a schematic diagram illustrating the design, preparation, and interfacial solvation structure of the bianion supramolecular eutectic gel electrolyte of the present invention. Figure 2 The formation states, differential scanning calorimetry, infrared and Raman spectra of eutectic solvents with different lithium salt 1 / lithium salt 2 / hydrogen bond donor ratios are shown. Figure 3 Figures showing the electrostatic potential, molecular dynamics, and density functional theory calculation results for monoanion systems, dianion systems, and biomass framework-dianion systems; Figure 4 A comparison of ion transport, electrochemical stability, and lithium deposition / stripping performance between monoanion supramolecular eutectic gel electrolytes and dianion supramolecular eutectic gel electrolytes. Figure 5 The diagram shows the cathode interface, lithium deposition morphology, lithium metal surface morphology, and interface chemical composition analysis after cycling with single-anion electrolyte and dual-anion electrolyte. Figure 6 The graph shows the rate performance and long-cycle performance of LFP and LCO lithium metal batteries assembled using single-anion electrolytes and dual-anion electrolytes. Detailed Implementation

[0020] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0021] like Figure 1 As shown, the biomass-based supramolecular eutectic gel electrolyte of this invention uses a bi-anionic eutectic solvent as the ion-conducting matrix and biomass materials as the supramolecular network framework. It is loaded onto a porous fiber carrier via in-situ cooling self-assembly, and can induce the formation of LiF, Li3N, and Li+-rich compounds at the positive and negative electrode interfaces of lithium metal batteries. x BᵧOFz's stable inorganic phase interface layer combines high ion conduction efficiency, a wide electrochemical window, and excellent interface stability.

[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments, enabling those skilled in the art to implement the invention accordingly. Where there is no conflict, the technical features in the following embodiments can be combined with each other.

[0023] The following examples are used to illustrate the present invention, but are not intended to limit the scope of protection of the present invention. Unless otherwise specified, all raw materials used are commercially available; LiTFSI represents lithium bis(trifluoromethanesulfonyl)imide, LiPF6 represents lithium hexafluorophosphate, LiFSI represents lithium bis(fluorosulfonyl)imide, LiBF4 represents lithium tetrafluoroborate, LiBOB represents lithium bis(oxalato)borate, LiODFB represents lithium difluorooxalatoborate, DMMN represents dimethylmalononitrile, SN represents succinic anionyl nitrile, NMA represents N-methylacetamide, TNMA represents N-methyl-2,2,2-trifluoroacetamide, HEC represents hydroxyethyl cellulose, Lignin represents lignin, CD represents cyclodextrin, CTS represents chitosan, Alg represents alginic acid, and FEC represents fluoroethylene carbonate.

[0024] The monoanion supramolecular eutectic gel electrolyte is denoted as SSDEE; the dianion supramolecular eutectic gel electrolyte is denoted as DSDEE.

[0025] Example 1 LiTFSI, LiODFB and DMMN were weighed in a molar ratio of 1:0.1:4 and added to a sealed reaction flask. The flask was heated and stirred at 300 r / min for 120 min in a 60℃ oil bath until the two lithium salts were completely dissolved, forming a homogeneous and transparent diaionic eutectic solvent.

[0026] Add 3 wt% of low-polymerization degree HEC to the above-mentioned diaionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 180 min until a homogeneous and viscous electrolyte precursor is formed. Depending on the interfacial film formation requirements, FEC can be added to the eutectic solvent before adding HEC, and stirred at a constant temperature for 30 min until uniformly dispersed before proceeding with subsequent operations.

[0027] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane. The amount of addition was controlled so that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment and allowed to cool for 60 min. This allowed HEC and the dianionic eutectic solvent to undergo in-situ self-assembly through hydrogen bonding and ionic dipole interaction, resulting in DSDEE.

[0028] Example 2 LiTFSI, LiBOB and SN were weighed in a molar ratio of 1:0.2:5 and added to a sealed reaction flask. The flask was heated and stirred at 300 r / min for 150 min in a 60℃ oil bath until the two lithium salts were completely dissolved, forming a homogeneous and transparent diaionic eutectic solvent.

[0029] Add 5 wt% of low-polymerization-degree Lignin to the above-mentioned bis-anionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 200 min until a homogeneous and viscous electrolyte precursor is formed. Depending on the interfacial film formation requirements, FEC can be added to the eutectic solvent before adding Lignin, and stirred at a constant temperature for 30 min until uniformly dispersed before proceeding with subsequent operations.

[0030] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane. The amount of addition was controlled so that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment and allowed to cool for 60 min. This allowed Lignin and the dianionic eutectic solvent to undergo in-situ self-assembly through hydrogen bonding and ionic dipole interaction, resulting in DSDEE.

[0031] Example 3 LiPF6, LiODFB and NMA were weighed in a molar ratio of 1:0.3:3 and added to a sealed reaction flask. The flask was heated and stirred at 300 r / min for 120 min in a 60℃ oil bath until the two lithium salts were completely dissolved, forming a homogeneous and transparent diaionic eutectic solvent.

[0032] Add 7 wt% of low-polymerization degree CD to the above-mentioned diaionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 180 min until a homogeneous and viscous electrolyte precursor is formed. Depending on the interfacial film formation requirements, FEC can be added to the eutectic solvent before adding CD, and stirred at a constant temperature for 30 min until uniformly dispersed before proceeding with subsequent operations.

[0033] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane. The amount of addition was controlled so that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment and allowed to cool for 60 min. This allowed CD and the dianionic eutectic solvent to undergo in-situ self-assembly through hydrogen bonding and ionic dipole interaction to obtain DSDEE.

[0034] Example 4 LiFSI, LiBF4 and TNMA were weighed in a molar ratio of 1:0.4:2 and added to a sealed reaction flask. The flask was heated and stirred at 300 r / min for 120 min in a 60℃ oil bath until the two lithium salts were completely dissolved, forming a homogeneous and transparent diaionic eutectic solvent.

[0035] Add 10 wt% of low-deacetylation CTS to the above-mentioned diaionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at 400 r / min for 200 min until a homogeneous and viscous electrolyte precursor is formed. FEC can be further added to the system as an auxiliary film-forming additive, and stirred at a constant temperature for 30 min until uniformly dispersed to form an electrolyte precursor with suitable viscosity.

[0036] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane, controlling the amount added to ensure that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment for 60 min to cool. After cooling, a DSDEE with a dynamic supramolecular network was formed. The electrolyte obtained in this example was used for subsequent structural, electrochemical, and battery performance testing.

[0037] Example 5 Weigh LiTFSI, LiODFB and NMA in a molar ratio of 1:0.5:3 and add them to a sealed reaction flask. Place the flask in a 60°C oil bath and heat and stir at 300 r / min for 150 min until the two lithium salts are completely dissolved to form a homogeneous and transparent diaionic eutectic solvent.

[0038] Add 10 wt% of low-polymerization degree Alg to the above-mentioned diaionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 180 min until a homogeneous and viscous electrolyte precursor is formed. Depending on the interfacial film formation requirements, FEC can be added to the eutectic solvent before adding Alg, and stirred at a constant temperature for 30 min until uniformly dispersed before proceeding with subsequent operations.

[0039] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane. The amount of addition was controlled so that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment and allowed to cool for 60 min. This allowed Alg and the dianionic eutectic solvent to undergo in-situ self-assembly through hydrogen bonding and ionic dipole interaction, resulting in DSDEE.

[0040] Example 6 LiTFSI, LiBF4 and DMMN were weighed in a molar ratio of 1:0.5:1 and added to a sealed reaction flask. The flask was heated and stirred at 300 r / min for 150 min in a 60℃ oil bath until the two lithium salts were completely dissolved, forming a homogeneous and transparent diaionic eutectic solvent.

[0041] Add 7 wt% of low-polymerization degree HEC to the above-mentioned diaionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 180 min until a homogeneous and viscous electrolyte precursor is formed. Depending on the interfacial film formation requirements, FEC can be added to the eutectic solvent before adding HEC, and stirred at a constant temperature for 30 min until uniformly dispersed before proceeding with subsequent operations.

[0042] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane. The amount of addition was controlled so that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment and allowed to cool for 60 min. This allowed HEC and the dianionic eutectic solvent to undergo in-situ self-assembly through hydrogen bonding and ionic dipole interaction, resulting in DSDEE.

[0043] To highlight the technical effects of introducing a second lithium salt to construct a dual anion solvation structure, the following comparative examples were set up. The only difference between each comparative example and the corresponding embodiment is that the comparative examples use only a single lithium salt (without adding a second lithium salt). The types of other components, molar ratios (with the second lithium salt counted as "0"), biomass materials and their amounts, preparation steps, and process parameters are all consistent with the corresponding embodiments to eliminate interference from other variables and ensure the reliability of the comparison results. The products obtained in each comparative example are denoted as SSDEE (single anion supramolecular eutectic gel electrolyte).

[0044] Comparative Example 1 Weigh LiTFSI and DMMN in a molar ratio of 1:4 and add them to a sealed reaction flask. Place the flask in a 60°C oil bath and heat and stir at 300 r / min for 120 min until the lithium salt is completely dissolved, forming a homogeneous and transparent monoanionic eutectic solvent.

[0045] Add 3 wt% of low-polymerization degree HEC to the above monoanionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 180 min until a homogeneous and viscous electrolyte precursor is formed.

[0046] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane, controlling the amount added to ensure that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment for 60 min to cool and obtain SSDEE. The electrolyte contains Li... + The first solvation layer is mainly composed of Li. + -TFSI - -DMMN structure, does not have ODFB - The participating bi-anion coordination structure.

[0047] Comparative Example 2 Weigh LiTFSI and SN in a molar ratio of 1:5 and add them to a sealed reaction flask. Place the flask in a 60°C oil bath and heat and stir at 300 r / min for 150 min until the lithium salt is completely dissolved, forming a homogeneous and transparent monoanionic eutectic solvent.

[0048] Add 5 wt% of low-polymerization-degree Lignin to the above monoanionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 200 min until a homogeneous and viscous electrolyte precursor is formed.

[0049] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane, controlling the amount added to ensure that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment for 60 min to cool and obtain SSDEE. The electrolyte contains Li... + The first solvation layer is mainly composed of Li. + -TFSI - -SN structure, does not have BOB - The participating bi-anion coordination structure.

[0050] Comparative Example 3 Weigh LiPF6 and NMA in a molar ratio of 1:3 and add them to a sealed reaction flask. Place the flask in a 60°C oil bath and heat and stir at 300 r / min for 120 min until the lithium salt is completely dissolved, forming a homogeneous and transparent monoanionic eutectic solvent.

[0051] Add 7 wt% of low-polymerization degree CD to the above monoanionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at a speed of 400 r / min for 180 min until a homogeneous and viscous electrolyte precursor is formed.

[0052] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane, controlling the amount added to ensure that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment for 60 min to cool and obtain SSDEE. The electrolyte contains Li... + The first solvation layer is mainly composed of Li. + -PF6 - -NMA structure, does not have ODFB - The participating bi-anion coordination structure.

[0053] Comparative Example 4 Weigh LiFSI and TNMA in a molar ratio of 1:2 and add them to a sealed reaction flask. Place the flask in a 60°C oil bath and heat and stir at 300 r / min for 120 min until the lithium salt is completely dissolved, forming a homogeneous and transparent monoanionic eutectic solvent.

[0054] Add 10 wt% of low-deacetylation CTS to the above monoanionic eutectic solvent, maintain a constant temperature of 60°C and continue stirring at 400 r / min for 200 min until a homogeneous and viscous electrolyte precursor is formed.

[0055] A 19 mm diameter glass fiber membrane was laid flat in a clean mold. The electrolyte precursor was added dropwise to the surface of the glass fiber membrane, controlling the amount added to ensure that the precursor completely wetted the carrier without excess overflow. The mold was then placed in a 25°C room temperature environment for 60 min to cool and obtain SSDEE. The electrolyte contains Li... + The first solvation layer is mainly composed of Li. + -FSI - -TNMA structure, does not have BF4 - The participating bi-anion coordination structure.

[0056] The following table compares the system compositions of the examples and comparative examples: ; As shown in the table above, each comparative example and the corresponding embodiment used the same main lithium salt, hydrogen bond donor, biomass skeleton and addition ratio. The only variable was whether a second lithium salt was introduced to construct a dual anion solvation system, which can directly compare and verify the regulatory effect of the dual anion structure on electrolyte performance. All comparative examples were single anion systems, which did not have a dual anion coordination solvation structure inside, and could not induce the formation of a high content inorganic phase interface layer at the electrode interface.

[0057] To systematically evaluate the comprehensive performance of the dual-anion supramolecular eutectic gel electrolyte (DSDEE) obtained in this invention and to directly compare it with the single-anion system (SSDEE), the following experimental examples were set up. All experimental examples used the same test methods, instrument conditions, battery assembly procedures, and environmental parameters to ensure the objectivity and reliability of the comparative data. Unless otherwise specified, all test data involved in the experimental examples were obtained at room temperature (25°C).

[0058] Experimental Example 1: Analysis of Eutectic Solvent Formation and Solvation Structure like Figure 2 As shown, mixing LiTFSI, LiODFB, and DMMN in the above proportions can all form a eutectic solvent under heating conditions, with melting points lower than those of the individual components. The -C≡N stretching vibration peak of DMMN is observed at 2253 cm⁻¹. -1Derived at 2284cm -1 The solvation peak of LiODFB; the C=O stretching vibration peak of LiODFB is from 1643 cm⁻¹. -1 Moved to 1638cm -1 This indicates that DMMN and ODFB - Participating in Li + Coordination.

[0059] Raman results showed that TFSI increased with increasing LiODFB content. - and ODFB - Participating in Li + As the degree of solvation of the sheath increases, the proportion of DMMN in the primary solvation layer decreases. When the ratio of LiTFSI:LiODFB:DMMN is 1:0.4:4, both anions fully participate in coordination and the system maintains good homogeneity. Further increasing the LiODFB content will lead to insufficient dissociation of some lithium salts and reduce ionic conductivity. At this ratio, DES is the preferred system.

[0060] like Figure 3 As shown, molecular dynamics simulations indicate that Li in SSDEE + With TFSI - The coordination distances of the O atom in DMMN and the N atom in DMMN are 1.90 Å and 2.06 Å, respectively, with corresponding coordination numbers of 3.072 and 2.165; in DSDEE, Li + With ODFB - The coordination distance of the O atom in Li is 1.88 Å, and the coordination number is 0.627. + The coordination distance with the N atom in DMMN increased to 2.08 Å, while the coordination number decreased to 1.948, proving that the first solvation layer was formed by Li. + -TFSI - -DMMN reconstructed into Li + -ODFB - -TFSI - -DMMN.

[0061] Experimental Example 2: Ion Transport and Electrochemical Stability like Figure 4 As shown, at 30°C, the ionic conductivity of SSDEE and the DSDEE obtained in Example 1 are 2.17 mS·cm, respectively. -1 and 1.66 mS·cm -1 The activation energy for ion transport in DSDEE is 0.218 eV, and the Li + The migration number was 0.75, significantly higher than SSDEE's 0.43, indicating that the dianionosolventization structure inhibits the migration of free anions and reduces concentration polarization.

[0062] Linear sweep voltammetry showed that the electrochemical stability window of the SSDEE was approximately 4.5 V, while the electrochemical stability window of the DSDEE obtained in Example 1 extended to approximately 5.2 V. When the electrolyte was used in an LCO||Li battery and voltage hold-up tests were performed at progressively higher voltages from 4.1 to 5.0 V, the leakage current of the DSDEE system was less than 10 μA below 5.0 V, indicating good compatibility with the high-voltage cathode.

[0063] At 0.2mA·cm -2 Current density and 0.2 mAh·cm -2 At the areal capacity, the Li||SSDEE||Li symmetric cell experienced a short circuit after approximately 500 hours; the Li||DSDEE||Li symmetric cell achieved stable cycling for over 3500 hours, with an average overpotential of approximately 39 mV. At 0.5 mA·cm⁻¹ -2 0.5mAh·cm -2 Under these conditions, Li||DSDEE||Li can still cycle stably for over 1000 hours. The exchange current density of the DSDEE system is 0.397 mA·cm⁻¹. -2 It is higher than the 0.079 mA·cm of the SSDEE system. -2 .

[0064] Experimental Example 3: Electrode Interface Composition and Lithium Deposition Morphology like Figure 5 As shown, after SSDEE cycling, LFP and LCO particles formed rough and unevenly thick CEI layers, with maximum thicknesses of approximately 4.5 nm and 4.9 nm, respectively. After DSDEE cycling, the CEI layers were thinner and more uniform, with maximum thicknesses of approximately 2.8 nm and 3.1 nm, respectively. EDS results showed that N, F, and B elements were more enriched at the interface after DSDEE cycling.

[0065] In the Li||SSDEE||Cu battery, dendritic lithium and cracks appeared on the copper foil surface; in the Li||DSDEE||Cu battery, the lithium deposition layer was dense, continuous, and relatively smooth, mainly exhibiting a uniform ellipsoidal or spherical structure. The lithium metal surface after Li||DSDEE||Li cycling was also relatively smooth, without obvious cracks, indicating that the dual anion solvation structure can suppress dendrite and dead lithium formation.

[0066] XPS depth analysis showed that the SEI induced by DSDEE was rich in LiF, Li3N and Li x BᵧOFz consists of an inorganic inner layer and an organic outer layer with elastic cushioning. The inorganic inner layer provides high mechanical strength and rapid Li + The conductive phase, an organic outer layer, buffers the volume changes caused by lithium deposition / stripping, thereby maintaining interface integrity.

[0067] Experimental Example 4: Performance of Lithium Metal Full Cells like Figure 6 As shown, a Li||DSDEE||LFP battery was assembled using the DSDEE obtained in Example 1, with a positive electrode active material loading of 1.7 mg·cm³. -2 The voltage range is 2.5-4.0V. This battery maintains a high specific capacity at rates from 0.1C to 5C, with a reversible specific capacity of 111.1 mAh·g at 5C. -1 After 1000, 2000, and 3000 cycles at 1C, the capacity retention was 94.6%, 86.5%, and 75.9%, respectively, and the reversible capacity after 3000 cycles was still 100.4 mAh·g. -1 .

[0068] A Li||DSDEE||LCO cell was assembled using DSDEE, with an LCO loading of 1.9 mg·cm⁻¹. -2 After 1000 cycles at a voltage of 3.0–4.4V and a 0.5C rate, the reversible capacity is 122.1 mAh·g. -1 The capacity retention rate was 88.7%; when the cutoff voltage was increased to 4.5V, the Li||DSDEE||LCO battery retained 78.2% of its capacity after 1000 cycles at 0.5C rate.

[0069] The following table compares the core properties of monoanion and dianion gel electrolytes: ; As can be seen from the table above, compared to the single-anion system SSDEE, the dual-anion system DSDEE of this invention, although exhibiting a slight decrease in room temperature ionic conductivity, still... + The migration number is increased by more than 74%, the electrochemical stability window is widened by 0.7V, the cycle life of lithium metal symmetric batteries is improved by more than 6 times, and it exhibits excellent long-term cycle stability in both LFP and LCO full cell systems. It can be adapted to both conventional voltage and high voltage cathode systems, and its overall performance is significantly better than existing single anion biomass gel electrolytes.

[0070] In summary, the above embodiments, comparative examples, and experimental results demonstrate that the present invention, by introducing a second lithium salt to construct a di-anionic eutectic solvent, reconstructs Li... + The first solvation layer, combined with the dynamic supramolecular network formed by the cooling self-assembly of biomass materials, can simultaneously achieve ion transport regulation and electrode interface modification. The dual anion system provides sufficient F, N, and B film-forming elements to the positive and negative electrode interfaces, inducing the formation of a dense interface layer with high inorganic phase content, effectively suppressing interfacial side reactions and lithium dendrite growth; the dynamic supramolecular network serves as both a Li… +It provides a continuous migration channel and can adapt to volume changes during electrode charging and discharging, maintaining the integrity of the electrolyte structure. The preparation process of this invention does not require covalent cross-linking and polymerization initiation steps, the process is simple and compatible with existing lithium battery manufacturing processes, and the resulting electrolyte has high safety, a wide electrochemical window and long cycle life, effectively solving the technical problem of the difficulty in balancing ion transport and interface stability in existing biomass-based gel electrolytes.

[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. Preparation of biomass-based supramolecular eutectic gel electrolyte, characterized in that, The preparation includes the following steps: S1. Lithium salt 1 and lithium salt 2, which act as hydrogen bond acceptors, are mixed with hydrogen bond donors and heated and stirred until a homogeneous and transparent dianionic eutectic solvent is formed. S2. Add biomass material as a framework network to a dianionic eutectic solvent and heat and stir until a homogeneous and viscous electrolyte precursor is formed. S3. The electrolyte precursor is applied to a porous fiber carrier and cooled to allow the biomass material and the dianionic eutectic solvent to self-assemble in situ through hydrogen bonding and ionic dipole interaction, thus obtaining a biomass-based supramolecular eutectic gel electrolyte.

2. The preparation of the biomass-based supramolecular eutectic gel electrolyte according to claim 1, characterized in that, In step S1, lithium salt 1 is selected from lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, and lithium difluorooxalate borate; lithium salt 2 is selected from lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, and lithium difluorooxalate borate; the hydrogen bond donor is selected from one or more of succinic anionyl, dimethylmalonium, N-methylacetamide, and N-methyl-2,2,2-trifluoroacetamide; and the biomass material in step S2 is selected from one or more of hydroxyethyl cellulose, lignin, cyclodextrin, chitosan, and alginate.

3. The preparation of the biomass-based supramolecular eutectic gel electrolyte according to claim 1, characterized in that, In step S1, the molar ratio of lithium salt 1 to lithium salt 2 is 1:0.1-0.5, the molar ratio of lithium salt 1 to hydrogen bond donor is 1:1-5, and the heating and stirring temperature is 50-70℃.

4. The preparation of the biomass-based supramolecular eutectic gel electrolyte according to claim 1, characterized in that, In step S2, the amount of biomass material added is 3-10 wt% of the total mass of the dianionic eutectic solvent, and the biomass material is a biomass material with low crystallinity or low degree of polymerization.

5. The preparation of the biomass-based supramolecular eutectic gel electrolyte according to claim 1, characterized in that, The process involves adding fluoroethylene carbonate as a film-forming additive to a dianionic eutectic solvent before or after the addition of biomass materials.

6. The preparation of the biomass-based supramolecular eutectic gel electrolyte according to claim 1, characterized in that, The porous fiber carrier in step S3 is a glass fiber membrane. When the electrolyte precursor is applied to the porous fiber carrier, the application method is one of dripping, impregnation, scraping or in-situ injection.

7. The preparation of the biomass-based supramolecular eutectic gel electrolyte according to claim 1, characterized in that, In the preparation process of step S3, no covalent crosslinking agent, monomer and polymerization initiator are added. After cooling, the electrolyte precursor forms a dynamic supramolecular network by reversible non-covalent interaction, which includes hydrogen bonding and ionic dipole interaction.

8. A biomass-based supramolecular eutectic gel electrolyte, characterized in that, The biomass-based supramolecular eutectic gel electrolyte is prepared by any one of claims 1-7. The gel electrolyte contains lithium salt 1, lithium salt 2 and a hydrogen bond donor. The first solvation layer of lithium ions is a coordination structure of lithium ion-anion 1-anion 2-hydrogen bond donor. The biomass material constitutes a supramolecular network with reversible hydrogen bonding and ionic dipole interaction.

9. The biomass-based supramolecular eutectic gel electrolyte according to claim 8, characterized in that, The gel electrolyte has an ionic conductivity of 1.0-2.5 mS·cm at 30°C. -1 The lithium-ion transference number is 0.50-0.80, and the electrochemical stability window is not lower than 5.0V. After the gel electrolyte is in contact with the lithium metal electrode and undergoes charge-discharge cycles, a layer containing LiF, Li3N, and Li is formed on the surface of the lithium metal anode. x The BᵧOFz inorganic phase solid electrolyte interface layer forms a positive electrode surface containing LiF, Li3N and Li. x BᵧOFz inorganic phase positive electrolyte interface layer.

10. The application of the biomass-based supramolecular eutectic gel electrolyte according to any one of claims 8-9 in lithium metal batteries, characterized in that, The lithium metal battery includes a positive electrode, a lithium metal negative electrode, and a gel electrolyte disposed between the positive electrode and the lithium metal negative electrode. The active material of the positive electrode is lithium iron phosphate or lithium cobalt oxide.